Hydroclimate in the Pamirs Was Driven by Changes in Precipitation‐Evaporation Seasonality Since the Last Glacial Period - Aichner, Bernhard; Makhmudov, Zafar; Rajabov, Ilhomjon; Zhang, Qiong; Pausata, Francesco S. R.; Werner, Martin; Heinecke, Liv; Kuessner, Marie L.; Feakins, Sarah J.; Sachse, Dirk; Mischke, Steffen (Geophysical Research Letters, 2019)
Abstract The Central Asian Pamir Mountains (Pamirs) are a high‐altitude region sensitive to climatic change, with only few paleoclimatic records available. To examine the glacial‐interglacial hydrological changes in the region, we analyzed the geochemical parameters of a 31‐kyr record from Lake Karakul and performed a set of experiments with climate models to interpret the results. δD values of terrestrial biomarkers showed insolation‐driven trends reflecting major shifts of water vapor sources. For aquatic biomarkers, positive δD shifts driven by changes in precipitation seasonality were observed at ca. 31–30, 28–26, and 17–14 kyr BP. Multiproxy paleoecological data and modelling results suggest that increased water availability, induced by decreased summer evaporation, triggered higher lake levels during those episodes, possibly synchronous to northern hemispheric rapid climate events. We conclude that seasonal changes in precipitation‐evaporation balance significantly influenced the hydrological state of a large waterbody such as Lake Karakul, while annual precipitation amount and inflows remained fairly constant. , Plain Language Summary Lakes in arid Central Asia are particularly susceptible to the rise and fall of lake levels as a consequence of climatic changes. To evaluate drivers behind this phenomenon, we developed a record of humidity and lake levels throughout the last 31,000 years from a high‐altitude lake in the Pamir Mountains. Herefore, we combined hydrological and ecological reconstructions with climate model experiments. Results show that neither the enhanced inflow by melting glaciers nor the significantly increased precipitation amount was responsible for higher lake levels during the studied interval. Instead, reduced summer evaporation during cold episodes was the major trigger for lake transgressions. These fluctuations were driven by changes in radiative forcing (i.e., insolation and hence temperature change) as a consequence of changes in the Earth's orbit around the Sun. As such, our results suggest that a significant impact on lake levels in arid regions is also to be expected by the current anthropogenically driven global warming. , Key Points Proxies for hydroclimate and catchment ecology show insolation‐driven trends, with higher δD values during the LGM similar to outputs from climate models Reduced summer evaporation during cold episodes increased water availability Increased summer moisture caused higher lake levels at 31–30, 28–26, and 17–14 kyr BP coinciding with northern hemispheric rapid climate events

Pervasive decreases in living vegetation carbon turnover time across forest climate zones - Yu, Kailiang; Smith, William K.; Trugman, Anna T.; Condit, Richard; Hubbell, Stephen P.; Sardans, Jordi; Peng, Changhui; Zhu, Kai; Peñuelas, Josep; Cailleret, Maxime; Levanic, Tom; Gessler, Arthur; et al. (Proceedings of the National Academy of Sciences, 2019)
Forests play a major role in the global carbon cycle. Previous studies on the capacity of forests to sequester atmospheric CO 2 have mostly focused on carbon uptake, but the roles of carbon turnover time and its spatiotemporal changes remain poorly understood. Here, we used long-term inventory data (1955 to 2018) from 695 mature forest plots to quantify temporal trends in living vegetation carbon turnover time across tropical, temperate, and cold climate zones, and compared plot data to 8 Earth system models (ESMs). Long-term plots consistently showed decreases in living vegetation carbon turnover time, likely driven by increased tree mortality across all major climate zones. Changes in living vegetation carbon turnover time were negatively correlated with CO 2 enrichment in both forest plot data and ESM simulations. However, plot-based correlations between living vegetation carbon turnover time and climate drivers such as precipitation and temperature diverged from those of ESM simulations. Our analyses suggest that forest carbon sinks are likely to be constrained by a decrease in living vegetation carbon turnover time, and accurate projections of forest carbon sink dynamics will require an improved representation of tree mortality processes and their sensitivity to climate in ESMs.

Greenland Ice Sheet mass loss rate will exceed Holocene values this century - Briner, J. P.; Cuzzone, J. K.; Badgeley, J.; Allan, E.; Bennike, O.; Cluett, A.; Csatho, B. M.; de Vernal, A.; Downs, J.; Hakim, G. J.; Johnson, J. V.; Larour, E. Y.; et al. (2019)
The Greenland Ice Sheet (GrIS) is a major contributor to sea level rise and may already be in irreversible decline. Observations spanning recent decades show the GrIS losing mass at an increasing rate; however, projecting this trend into the future is complicated by year-to-year variability and requires looking at longer timescales. Historical data suggest the GrIS was nearly in balance in the 1800s (-900 Gt/century), but had negative balance in the 1900s (-4000 to -8000 Gt/century). Projecting observations made thus far from the 2000s, mass-loss rate could average anywhere from ca. -40,000 to -100,000 Gt/century. Our goal is to evaluate these historic and contemporary rates of GrIS mass loss within the framework of the current Holocene interglacial spanning the last 12,000 years. To do so we combine the first highly resolved paleo-GrIS simulations using NASA's Ice Sheet System Model with novel climate forcing based on a data assimilation approach using multiple paleoclimate records. Our new simulations take place across a glaciologically simple domain in SW Greenland (encompassing ca. 30% of the ice sheet), where they are validated with our detailed glacial chronology of Holocene ice margin change. During the Holocene thermal maximum, a period between ca. 10,000 and 8000 years ago, the GrIS experienced elevated mass loss rates, with maximum values on the order of -5000 to -10,000 Gt/century for our model domain. When these values are scaled to the entire GrIS (using the proportion of SW mass loss vs. total GrIS mass loss from contemporary studies), they equate to maximum mass loss rates of ca. -20,000 to -40,000 Gt/century. From this we conclude that the rate of GrIS mass loss will exceed Holocene values this century.
Conference Name: AGU Fall Meeting Abstracts ADS Bibcode: 2019AGUFM.C11B..06B
Keywords: 0726 Ice sheets; 1616 Climate variability; 1621 Cryospheric change; 1641 Sea level change; CRYOSPHERE; GLOBAL CHANGE

Carbon and Water Use Efficiencies: A Comparative Analysis of Ten Terrestrial Ecosystem Models under Changing Climate - El Masri, Bassil; Schwalm, Christopher; Huntzinger, Deborah N.; Mao, Jiafu; Shi, Xiaoying; Peng, Changhui; Fisher, Joshua B.; Jain, Atul K.; Tian, Hanqin; Poulter, Benjamin; Michalak, Anna M. (Scientific Reports, 2019)
Abstract Terrestrial ecosystems carbon and water cycles are tightly coupled through photosynthesis and evapotranspiration processes. The ratios of carbon stored to carbon uptake and water loss to carbon gain are key ecophysiological indicators essential to assess the magnitude and response of the terrestrial plant to the changing climate. Here, we use estimates from 10 terrestrial ecosystem models to quantify the impacts of climate, atmospheric CO 2 concentration, and nitrogen (N) deposition on water use efficiency (WUE), and carbon use efficiency (CUE). We find that across models, WUE increases over the 20 th Century particularly due to CO 2 fertilization and N deposition and compares favorably to experimental studies. Also, the results show a decrease in WUE with climate for the last 3 decades, in contrasts with up-scaled flux observations that demonstrate a constant WUE. Modeled WUE responds minimally to climate with modeled CUE exhibiting no clear trend across space and time. The divergence between simulated and observationally-constrained WUE and CUE is driven by modeled NPP and autotrophic respiration, nitrogen cycle, carbon allocation, and soil moisture dynamics in current ecosystem models. We suggest that carbon-modeling community needs to reexamine stomatal conductance schemes and the soil-vegetation interactions for more robust modeling of carbon and water cycles.

Role of sublimation and riming in the precipitation distribution in the Kananaskis Valley, Alberta, Canada - Poirier, Émilie; Thériault, Julie M.; Leriche, Maud (Hydrology and Earth System Sciences, 2019)
Abstract. The phase of precipitation and its distribution at the surface can affect water resources and the regional water cycle of a region. A field project was held in March–April 2015 on the eastern slope of the Canadian Rockies to document precipitation characteristics and associated atmospheric conditions. During the project, 60 % of the particles documented were rimed in relatively warm and dry conditions. Rain–snow transitions also occurred aloft and at the surface in sub-saturated conditions. Ice-phase precipitation falling through a saturated atmospheric layer with temperatures > 0 ∘C will start melting. In contrast, if the melting layer is sub-saturated, the ice-phase precipitation undergoes sublimation, which increases the depth of the rain–snow transition. In this context, this study investigates the role of sublimation and riming in precipitation intensity and type reaching the surface in the Kananaskis Valley, Alberta, during March–April 2015. To address this, a set of numerical simulations of an event of mixed precipitation observed at the surface was conducted. This event on 31 March 2015 was documented with a set of devices at the main observation site (Kananaskis Emergency Services, KES), including a precipitation gauge, disdrometer, and micro rain radar. Sensitivity experiments were performed to assess the impacts of temperature changes from sublimation and the role of the production of graupel (riming) aloft in the surface precipitation evolution. A warmer environment associated with no temperature changes from sublimation leads to a peak in the intensity of graupel at the surface. When the formation of graupel is not considered, the maximum snowfall rate occurred at later times. Results suggest that unrimed snow reaching the surface is formed on the western flank and is advected eastward. In contrast, graupel would form aloft in the Kananaskis Valley. The cooling from sublimation and melting by rimed particles increases the vertical shear near KES. Overall, this study illustrated that the presence of graupel influenced the surface evolution of precipitation type in the valley due to the horizontal transport of precipitation particles.

Northern Hemisphere Land Monsoon Precipitation Increased by the Green Sahara During Middle Holocene - Sun, Weiyi; Wang, Bin; Zhang, Qiong; Pausata, Francesco S. R.; Chen, Deliang; Lu, Guonian; Yan, Mi; Ning, Liang; Liu, Jian (Geophysical Research Letters, 2019)
Abstract Changes in land cover and dust emission may significantly influence the Northern Hemisphere land monsoon precipitation (NHLMP), but observations are too short to fully evaluate their impacts. The “Green Sahara” during the mid‐Holocene (6,000 years BP) provides an opportunity to unravel these mechanisms. Here we show that during the mid‐Holocene, most of the NHLMP changes revealed by proxy data are reproduced by the Earth System model results when the Saharan vegetation cover and dust reduction are taken into consideration. The simulated NHLMP significantly increases by 33.10% under the effect of the Green Sahara. The North African monsoon precipitation increases most significantly. Additionally, the Saharan vegetation (dust reduction under vegetated Sahara) alone remotely intensifies the Asian (North American) monsoon precipitation through large‐scale atmospheric circulation changes. These findings imply that future variations in land cover and dust emissions may appreciably influence the NHLMP. , Plain Language Summary Northern Hemisphere land monsoon precipitation (NHLMP) provides water resources for about two thirds of the world's population, which is vital for infrastructure planning, disaster mitigation, food security, and economic development. Changes in land cover and dust emissions may significantly influence the NHLMP, but observations are too short to understand the mechanisms. The Sahara Desert was once covered by vegetation and dust emission was substantially reduced during the mid‐Holocene (6,000 years BP), which provides an opportunity to test the models' capability and unravel these mechanisms. Here we use an Earth System model and find that when the Saharan vegetation and dust reduction are taken into consideration, the simulated annual mean precipitation over most of the NHLM regions shows a closer agreement with proxy records. The sensitivity experiments show that the North African monsoon precipitation increases most significantly under the regional effects of “Green Sahara.” The Saharan vegetation (dust reduction under vegetated Sahara) alone also remotely increases the Asian (North American) monsoon precipitation through large‐scale atmospheric circulation changes. The knowledge gained from this study is critical for improved understanding of the potential impacts of the land cover and dust changes on the projected future monsoon change. , Key Points The first study of the impact of Saharan vegetation and dust reduction on the NHLMP Comparison with proxy records shows the effect of the Green Sahara improves the simulated NHLMP The Saharan vegetation and dust reduction significantly increase the NHLMP by 33.10%

Separating Regressions for Model Fitting to Reduce the Uncertainty in Forest Volume-Biomass Relationship - Liu, Caixia; Zhou, Xiaolu; Lei, Xiangdong; Huang, Huabing; Zhou, Carl; Peng, Changhui; Wang, Xiaoyi (Forests, 2019)
The method of forest biomass estimation based on a relationship between the volume and biomass has been applied conventionally for estimating stand above- and below-ground biomass (SABB, t ha−1) from mean growing stock volume (m3 ha−1). However, few studies have reported on the diagnosis of the volume-SABB equations fitted using field data. This paper addresses how to (i) check parameters of the volume-SABB equations, and (ii) reduce the bias while building these equations. In our analysis, all equations were applied based on the measurements of plots (biomass or volume per hectare) rather than individual trees. The volume-SABB equation is re-expressed by two Parametric Equations (PEs) for separating regressions. Stem biomass is an intermediate variable (parametric variable) in the PEs, of which one is established by regressing the relationship between stem biomass and volume, and the other is created by regressing the allometric relationship of stem biomass and SABB. A graphical analysis of the PEs proposes a concept of “restricted zone,” which helps to diagnose parameters of the volume-SABB equations in regression analyses of field data. The sampling simulations were performed using pseudo data (artificially generated in order to test a model) for the model test. Both analyses of the regression and simulation demonstrate that the wood density impacts the parameters more than the allometric relationship does. This paper presents an applicable method for testing the field data using reasonable wood densities, restricting the error in field data processing based on limited field plots, and achieving a better understanding of the uncertainty in building those equations.

Simulating Arctic Ice Clouds during Spring Using an Advanced Ice Cloud Microphysics in the WRF Model - Keita, Setigui; Girard, Eric; Raut, Jean-Christophe; Pelon, Jacques; Blanchet, Jean-Pierre; Lemoine, Olivier; Onishi, Tatsuo (Atmosphere, 2019)
Two Types of Ice Clouds (TICs) have been characterized in the Arctic during the polar night and early spring. TIC-1 are composed by non-precipitating small ice crystals of less than 30 µm in diameter. The second type, TIC-2, are characterized by a low concentration of large precipitating ice crystals (>30 µm). Here, we evaluate the Weather Research and Forecasting (WRF) model performance both in space and time after implementing a parameterization based on a stochastic approach dedicated to the simulation of ice clouds in the Arctic. Well documented reference cases provided us in situ data from the spring of 2008 Indirect and Semi-Direct Aerosol Campaign (ISDAC) campaign over Alaska. Simulations of the microphysical properties of the TIC-2 clouds on 15 and 25 April 2008 (polluted or acidic cases) and TIC-1 clouds on non-polluted cases are compared to DARDAR (raDAR/liDAR) satellite products. Our results show that the stochastic approach based on the classical nucleation theory, with the appropriate contact angle, is better than the original scheme in WRF model to represent TIC-1 and TIC-2 properties (ice crystal concentration and size) in response to the IN acidification.
Keywords: Arctique; Atmosphère

Trait-Based Climate Change Predictions of Vegetation Sensitivity and Distribution in China - Yang, Yanzheng; Zhao, Jun; Zhao, Pengxiang; Wang, Hui; Wang, Boheng; Su, Shaofeng; Li, Mingxu; Wang, Liming; Zhu, Qiuan; Pang, Zhiyong; Peng, Changhui (Frontiers in Plant Science, 2019)

Exposures to temperature beyond threshold disproportionately reduce vegetation growth in the northern hemisphere - Wu, Xiuchen; Guo, Weichao; Liu, Hongyan; Li, Xiaoyan; Peng, Changhui; Allen, Craig D; Zhang, Cicheng; Wang, Pei; Pei, Tingting; Ma, Yujun; Tian, Yuhong; Song, Zhaoliang; et al. (National Science Review, 2019)
Abstract In recent decades, terrestrial vegetation in the northern hemisphere (NH) has been exposed to warming and more extremely high temperatures. However, the consequences of these changes for terrestrial vegetation growth remain poorly quantified and understood. By examining a satellite-based vegetation index, tree-ring measurements and land-surface model simulations, we discovered a consistent convex pattern in the responses of vegetation growth to temperature exposure (TE) for forest, shrub and grass in both the temperate (30°−50° N) and boreal (50°−70° N) NH during the period of 1982−2012. The response of vegetation growth to TE for the three vegetation types in both the temperate and boreal NH increased convergently with increasing temperature, until vegetation type-dependent temperature thresholds were reached. A TE beyond these temperature thresholds resulted in disproportionately weak positive or even strong negative responses. Vegetation growth in the boreal NH was more vulnerable to extremely high-temperature events than vegetation growth in the temporal NH. The non-linear responses discovered here provide new insights into the dynamics of northern terrestrial ecosystems in a warmer world.

Variations of Sediment Archaea Communitiesin Different Distribution Areasof Bruguiera gymnoihiza Mangrovein Dongzhaigang, China - Li, Wei; Guan, Wei; Chen, Huai; Liao, Baowen; Hu, Ji; Rui, Junpeng; Peng, Changhui; Zhu, Dan; He, Yixin; Tian, Jianqing (Polish Journal of Environmental Studies, 2019)

Risk assessment strategies for early detection and prediction of infectious disease outbreaks associated with climate change - Rees, Ee; Ng, V; Gachon, P; Mawudeku, A; McKenney, D; Pedlar, J; Yemshanov, D; Parmely, J; Knox, J (Canada Communicable Disease Report, 2019)

Tropical cyclone activity affected by volcanically induced ITCZ shifts - Pausata, Francesco S. R.; Camargo, Suzana J. (Proceedings of the National Academy of Sciences, 2019)
Significance Volcanic eruptions can inject a large amount of aerosol particles, which interact with solar radiation and consequently can affect the climate worldwide, hence the intensity and frequency of extreme events for a few years following the eruption. However, only a handful of studies have investigated the impacts of volcanic eruptions on tropical cyclone activity. Through a set of sensitivity modeling experiments, our study demonstrates that volcanic eruptions by shifting the Intertropical convergence zone can impact tropical cyclone activity up to 4 years following the eruption. These results will prove valuable to society, allowing us to better prepare for the consequences of changes in tropical cyclone activity following large volcanic eruptions. , Volcanic eruptions can affect global climate through changes in atmospheric and ocean circulation, and therefore could impact tropical cyclone (TC) activity. Here, we use ensemble simulations performed with an Earth System Model to investigate the impact of strong volcanic eruptions occurring in the tropical Northern (NH) and Southern (SH) Hemisphere on the large-scale environmental factors that affect TCs. Such eruptions cause a strong asymmetrical hemispheric cooling, either in the NH or SH, which shifts the Intertropical Convergence Zone (ITCZ) southward or northward, respectively. The ITCZ shift and the associated surface temperature anomalies then cause changes to the genesis potential indices and TC potential intensity. The effect of the volcanic eruptions on the ITCZ and hence on TC activity lasts for at least 4 years. Finally, our analysis suggests that volcanic eruptions do not lead to an overall global reduction in TC activity but rather a redistribution following the ITCZ movement. On the other hand, the volcanically induced changes in El Niño-Southern Oscillation (ENSO) or sea-surface temperature do not seem to have a significant impact on TC activity as previously suggested.

Climate change and infectious diseases: What can we expect? - Ogden, Nh; Gachon, P (Canada Communicable Disease Report, 2019)

The water cycle of the mid‐Holocene West African monsoon: The role of vegetation and dust emission changes - Messori, Gabriele; Gaetani, Marco; Zhang, Qiang; Zhang, Qiong; Pausata, Francesco S. R. (International Journal of Climatology, 2019)
During the mid‐Holocene (6 kyr BP), West Africa experienced a much stronger and geographically extensive monsoon than in the present day. Changes in orbital forcing, vegetation and dust emissions from the Sahara have been identified as key factors driving this intensification. Here, we analyse how the timing, origin and convergence of moisture fluxes contributing to the monsoonal precipitation change under a range of scenarios: orbital forcing only; orbital and vegetation forcings (Green Sahara); orbital, vegetation and dust forcings (Green Sahara‐reduced dust). We further compare our results to a range of reconstructions of mid‐Holocene precipitation from palaeoclimate archives. In our simulations, the greening of the Sahara leads to a cyclonic water vapour flux anomaly over North Africa with an anomalous westerly flow bringing large amounts of moisture into the Sahel from the Atlantic Ocean. Changes in atmospheric dust under a vegetated Sahara shift the anomalous moisture advection pattern northwards, increasing both moisture convergence and precipitation recycling over the northern Sahel and Sahara and the associated precipitation during the boreal summer. During this season, under both the Green Sahara and Green Sahara‐reduced dust scenarios, local recycling in the Saharan domain exceeds that of the Sahel. This points to local recycling as an important factor modulating vegetation‐precipitation feedbacks and the impact of Saharan dust emissions. Our results also show that temperature and evapotranspiration over the Sahara in the mid‐Holocene are close to Sahelian pre‐industrial values. This suggests that pollen‐based paleoclimate reconstructions of precipitation during the Green Sahara period are likely not biased by possible large evapotranspiration changes in the region.

Influence of the Model Horizontal Resolution on Atmospheric Conditions Leading to Freezing Rain in Regional Climate Simulations - St-Pierre, Médéric; Thériault, Julie M.; Paquin, Dominique (Atmosphere-Ocean, 2019)

Overview paper: New insights into aerosol and climate in the Arctic - Abbatt, Jonathan P. D.; Leaitch, W. Richard; Aliabadi, Amir A.; Bertram, Allan K.; Blanchet, Jean-Pierre; Boivin-Rioux, Aude; Bozem, Heiko; Burkart, Julia; Chang, Rachel Y. W.; Charette, Joannie; Chaubey, Jai P.; Christensen, Robert J.; et al. (Atmospheric Chemistry and Physics, 2019)
Abstract. Motivated by the need to predict how the Arctic atmosphere will change in a warming world, this article summarizes recent advances made by the research consortium NETCARE (Network on Climate and Aerosols: Addressing Key Uncertainties in Remote Canadian Environments) that contribute to our fundamental understanding of Arctic aerosol particles as they relate to climate forcing. The overall goal of NETCARE research has been to use an interdisciplinary approach encompassing extensive field observations and a range of chemical transport, earth system, and biogeochemical models. Several major findings and advances have emerged from NETCARE since its formation in 2013. (1) Unexpectedly high summertime dimethyl sulfide (DMS) levels were identified in ocean water (up to 75 nM) and the overlying atmosphere (up to 1 ppbv) in the Canadian Arctic Archipelago (CAA). Furthermore, melt ponds, which are widely prevalent, were identified as an important DMS source (with DMS concentrations of up to 6 nM and a potential contribution to atmospheric DMS of 20 % in the study area). (2) Evidence of widespread particle nucleation and growth in the marine boundary layer was found in the CAA in the summertime, with these events observed on 41 % of days in a 2016 cruise. As well, at Alert, Nunavut, particles that are newly formed and grown under conditions of minimal anthropogenic influence during the months of July and August are estimated to contribute 20 % to 80 % of the 30–50 nm particle number density. DMS-oxidation-driven nucleation is facilitated by the presence of atmospheric ammonia arising from seabird-colony emissions, and potentially also from coastal regions, tundra, and biomass burning. Via accumulation of secondary organic aerosol (SOA), a significant fraction of the new particles grow to sizes that are active in cloud droplet formation. Although the gaseous precursors to Arctic marine SOA remain poorly defined, the measured levels of common continental SOA precursors (isoprene and monoterpenes) were low, whereas elevated mixing ratios of oxygenated volatile organic compounds (OVOCs) were inferred to arise via processes involving the sea surface microlayer. (3) The variability in the vertical distribution of black carbon (BC) under both springtime Arctic haze and more pristine summertime aerosol conditions was observed. Measured particle size distributions and mixing states were used to constrain, for the first time, calculations of aerosol–climate interactions under Arctic conditions. Aircraft- and ground-based measurements were used to better establish the BC source regions that supply the Arctic via long-range transport mechanisms, with evidence for a dominant springtime contribution from eastern and southern Asia to the middle troposphere, and a major contribution from northern Asia to the surface. (4) Measurements of ice nucleating particles (INPs) in the Arctic indicate that a major source of these particles is mineral dust, likely derived from local sources in the summer and long-range transport in the spring. In addition, INPs are abundant in the sea surface microlayer in the Arctic, and possibly play a role in ice nucleation in the atmosphere when mineral dust concentrations are low. (5) Amongst multiple aerosol components, BC was observed to have the smallest effective deposition velocities to high Arctic snow (0.03 cm s−1).

A Review and Synthesis of Future Earth System Change in theInterior of Western Canada: Part I – Climate and Meteorology - Stewart, Ronald E.; Szeto, Kit K.; Bonsal, Barrie R.; Hanesiak, John M.; Kochtubajda, Bohdan; Li, Yanping; Thériault, Julie M.; DeBeer, Chris M.; Tam, Benita Y.; Li, Zhenhua; Liu, Zhuo; Bruneau, Jennifer A.; et al. (Hydrometeorology/Modelling approaches, 2019)
Abstract. The Interior of Western Canada, up to and including the Arctic, has experienced rapid change in its climate, hydrology, cryosphere and ecosystems and this is expected to continue. Although there is general consensus that warming will occur in the future, many critical issues remain. In this first of two articles, attention is placed on atmospheric-related issues that range from large scales down to individual precipitation events. Each of these is considered in terms of expected change organized by season and utilizing climate scenario information as well as thermodynamically-driven future climatic forcing simulations. Large scale atmospheric circulations affecting this region are generally projected to become stronger in each season and, coupled with warming temperatures, lead to enhancements of numerous water-related and temperature-related extremes. These include winter snowstorms, freezing rain, drought as well as atmospheric forcing of spring floods although not necessarily summer convection. Collective insights of these atmospheric findings are summarized in a consistent, connected physical framework.

Parameterization of the Bulk Liquid Fraction on Mixed-Phase Particles in the Predicted Particle Properties (P3) Scheme: Description and Idealized Simulations - Cholette, Mélissa; Morrison, Hugh; Milbrandt, Jason A.; Thériault, Julie M. (Journal of the Atmospheric Sciences, 2019)
Abstract Bulk microphysics parameterizations that are used to represent clouds and precipitation usually allow only solid and liquid hydrometeors. Predicting the bulk liquid fraction on ice allows an explicit representation of mixed-phase particles and various precipitation types, such as wet snow and ice pellets. In this paper, an approach for the representation of the bulk liquid fraction into the predicted particle properties (P3) microphysics scheme is proposed and described. Solid-phase microphysical processes, such as melting and sublimation, have been modified to account for the liquid component. New processes, such as refreezing and condensation of the liquid portion of mixed-phase particles, have been added to the parameterization. Idealized simulations using a one-dimensional framework illustrate the overall behavior of the modified scheme. The proposed approach compares well to a Lagrangian benchmark model. Temperatures required for populations of ice crystals to melt completely also agree well with previous studies. The new processes of refreezing and condensation impact both the surface precipitation type and feedback between the temperature and the phase changes. Overall, prediction of the bulk liquid fraction allows an explicit description of new precipitation types, such as wet snow and ice pellets, and improves the representation of hydrometeor properties when the temperature is near 0°C.

Maximum likelihood estimation of first-passage structural credit risk models correcting for the survivorship bias - Amaya, Diego; Boudreault, Mathieu; McLeish, Don L. (Journal of Economic Dynamics and Control, 2019)

Impact of reanalysis boundary conditions on downscaled Atlantic hurricane activity - Baudouin, Jean-Philippe; Caron, Louis-Philippe; Boudreault, Mathieu (Climate Dynamics, 2019)

Credit and Systemic Risks in the Financial Services Sector: Evidence From the 2008 Global Crisis - Bégin, Jean‐François; Boudreault, Mathieu; Doljanu, Delia Alexandra; Gauthier, Geneviève (Journal of Risk and Insurance, 2019)
Abstract We develop a portfolio credit risk model that includes firm‐specific Markov‐switching regimes as well as individual stochastic and endogenous recovery rates. Using weekly credit default swap premiums for 35 financial firms, we analyze the credit risk of each of these companies and their statistical linkages, putting emphasis on the 2005–2012 period. Moreover, we study the systemic risk affecting both the banking and insurance subsectors.

Challenges and research priorities to understand interactions between climate, ice sheets and global mean sea level during past interglacials - Capron, Emilie; Rovere, Alessio; Austermann, Jacqueline; Axford, Yarrow; Barlow, Natasha L.M.; Carlson, Anders E.; De Vernal, Anne; Dutton, Andrea; Kopp, Robert E.; McManus, Jerry F.; Menviel, Laurie; Otto-Bliesner, Bette L.; et al. (Quaternary Science Reviews, 2019)

Climate changes in the Holocene: impact, adaptation, and resilience - Chiotis, Eustathios (CRC Press, 2019)
Climate change in the current geological era, from approximately 11,000 years ago to the present

Vegetation Functional Properties Determine Uncertainty of Simulated Ecosystem Productivity: A Traceability Analysis in the East Asian Monsoon Region - Cui, Erqian; Huang, Kun; Arain, Muhammad Altaf; Fisher, Joshua B.; Huntzinger, Deborah N.; Ito, Akihiko; Luo, Yiqi; Jain, Atul K.; Mao, Jiafu; Michalak, Anna M.; Niu, Shuli; Parazoo, Nicholas C.; et al. (Global Biogeochemical Cycles, 2019)
Abstract Global and regional projections of climate change by Earth system models are limited by their uncertain estimates of terrestrial ecosystem productivity. At the middle to low latitudes, the East Asian monsoon region has higher productivity than forests in Europe‐Africa and North America, but its estimate by current generation of terrestrial biosphere models (TBMs) has seldom been systematically evaluated. Here, we developed a traceability framework to evaluate the simulated gross primary productivity (GPP) by 15 TBMs in the East Asian monsoon region. The framework links GPP to net primary productivity, biomass, leaf area and back to GPP via incorporating multiple vegetation functional properties of carbon‐use efficiency (CUE), vegetation C turnover time ( τ veg ), leaf C fraction (F leaf ), specific leaf area (SLA), and leaf area index (LAI)‐level photosynthesis (P LAI ), respectively. We then applied a relative importance algorithm to attribute intermodel variation at each node. The results showed that large intermodel variation in GPP over 1901–2010 were mainly propagated from their different representation of vegetation functional properties. For example, SLA explained 77% of the intermodel difference in leaf area, which contributed 90% to the simulated GPP differences. In addition, the models simulated higher CUE (18.1 ± 21.3%), τ veg (18.2 ± 26.9%), and SLA (27.4±36.5%) than observations, leading to the overestimation of simulated GPP across the East Asian monsoon region. These results suggest the large uncertainty of current TBMs in simulating GPP is largely propagated from their poor representation of the vegetation functional properties and call for a better understanding of the covariations between plant functional properties in terrestrial ecosystems. , Key Points A GPP‐traceability framework is established to diagnose the uncertainty sources of modeled GPP Large intermodel differences of modeled GPP result from their different representation of vegetation functional properties Positive bias in simulated GPP over the East Asian monsoon region could be attributed to the higher simulated CUE and SLA comparing with observations

Millennial‐Scale Climate Variability and Dinoflagellate‐Cyst‐Based Seasonality Changes Over the Last ~150 kyrs at “Shackleton Site” U1385 - Datema, Mariska; Sangiorgi, Francesca; De Vernal, Anne; Reichart, Gert‐Jan; Lourens, Lucas J.; Sluijs, Appy (Paleoceanography and Paleoclimatology, 2019)
Abstract During the last glacial period, climate conditions in the North Atlantic region were determined by the alternation of relatively warm interstadials and relatively cool stadials, with superimposed rapid warming (Dansgaard‐Oeschger) and cooling (Heinrich) events. So far little is known about the impact of these rapid climate shifts on the seasonal variations in sea surface temperature (SST) within the North Atlantic region. Here, we present a high‐resolution seasonal SST record for the past 152 kyrs derived from Integrated Ocean Drilling Program “Shackleton” Site U1385, offshore Portugal. Assemblage counts of dinoflagellates cysts (dinocysts) in combination with a modern analog technique (MAT), and regression analyses were used for the reconstructions. We compare our records with previously published SST records from the same location obtained from the application of MAT on planktonic foraminifera. Our dinocyst‐based reconstructions confirm the impression of the Greenland stadials and interstadials offshore the Portuguese margin and indicate increased seasonal contrast of temperature during the cold periods of the glacial cycle (average 9.0 °C, maximum 12.2 °C) with respect to present day (5.1 °C), due to strong winter cooling by up to 8.3 °C. Our seasonal temperature reconstructions are in line with previously published data, which showed increased seasonality due to strong winter cooling during the Younger Dryas and the Last Glacial Maximum over the European continent and North Atlantic region. In addition, we show that over longer time scales, increased seasonal contrasts of temperature remained characteristic of the colder phases of the glacial cycle. , Key Points New high‐resolution dinocyst‐based summer and winter SST record from IODP “Shackleton” Site U1385 for the last 150 kyrs is presented Dinocyst‐based SST confirms the D‐O cycles and HEs at Site U1385 Increased seasonal contrast of SST (up to 12 degree C) during cold periods of the glacial cycle related to strong winter cooling is shown

Land-use changes driven by ‘Grain for Green’ program reduced carbon loss induced by soil erosion on the Loess Plateau of China - Deng, Lei; Kim, Dong-Gill; Li, Miaoyu; Huang, Chunbo; Liu, Qiuyu; Cheng, Min; Shangguan, Zhouping; Peng, Changhui (Global and Planetary Change, 2019)

Drivers of soil microbial metabolic limitation changes along a vegetation restoration gradient on the Loess Plateau, China - Deng, Lei; Peng, Changhui; Huang, Chunbo; Wang, Kaibo; Liu, Qiuyu; Liu, Yulin; Hai, Xuying; Shangguan, Zhouping (Geoderma, 2019)

Evaluating reanalysis-driven CORDEX regional climate models over Australia: model performance and errors - Di Virgilio, Giovanni; Evans, Jason P.; Di Luca, Alejandro; Olson, Roman; Argüeso, Daniel; Kala, Jatin; Andrys, Julia; Hoffmann, Peter; Katzfey, Jack J.; Rockel, Burkhardt (Climate Dynamics, 2019)

Review of Australian east coast low pressure systems and associated extremes - Dowdy, Andrew J.; Pepler, Acacia; Di Luca, Alejandro; Cavicchia, Leone; Mills, Graham; Evans, Jason P.; Louis, Simon; McInnes, Kathleen L.; Walsh, Kevin (Climate Dynamics, 2019)

Differences of soil CO2 flux in two contrasting subalpine ecosystems on the eastern edge of the Qinghai-Tibetan Plateau: A four-year study - Duan, Min; Li, Andi; Wu, Yanhong; Zhao, Zuoping; Peng, Changhui; DeLuca, Thomas H.; Sun, Shouqin (Atmospheric Environment, 2019)

Impact of climate change on Ostrinia nubilalis (Lepidoptera: Crambidae) phenology and its implications on pest management - Gagnon, Annie‐Ève; Bourgeois, Gaétan; Bourdages, Line; Grenier, Patrick; Blondlot, Anne (Agricultural and Forest Entomology, 2019)
Abstract Climate change can cause negative impacts to the agricultural sector by increasing pest damage to crops. The European corn borer (ECB) is a major insect pest of corn in North America. Its speed of development could potentially accelerate under a warmer climate, leading to an earlier development of the first generation and an increase in the number of generations per year. The main objective of this study was to assess the potential impacts of climate change on ECB management for the future period 2041–2070 in Quebec, Canada, using bioclimatic modelling and climate analogues. First flight of ECB moths could occur about 15 days earlier in the season in 2041–2070 compared to the reference period 1970–1999. The window for insecticide interventions may be reduced under climate change by 15.6% to 27.8% for univoltine ECB and by 13.8% to 52.7% for bivoltine ECB. Climate change could promote the development of an additional generation in the southern region for both races, considering temperature increases and factors inducing the overwintering diapause. ECB management could become more costly both economically and environmentally under the future climate, and it should be revised according to the results of this study.

A metrics‐based analysis of seasonal daily precipitation and near‐surface temperature within seven Coordinated Regional Climate Downscaling Experiment domains - Glisan, Justin M.; Jones, Richard; Lennard, Chris; Castillo Pérez, Nadia I.; Lucas‐Picher, Philippe; Rinke, Annette; Solman, Silvina; Gutowski, William J. (Atmospheric Science Letters, 2019)
We compare ensemble mean daily precipitation and near‐surface temperatures from regional climate model simulations over seven Coordinated Regional Climate Downscaling Experiment domains for the winter and summer seasons. We use Taylor diagrams to show the domain‐wide pattern similarity between the model ensemble and the observational data sets. We use the Climatic Research Unit (CRU) and the University of Delaware gridded observations and ERA‐Interim reanalysis data as an additional observationally based estimate of historical climatology. Taylor diagrams determine the relative skill of the seven sets of simulations and quantify these results in terms of center pattern root‐mean square error and correlation coefficient. Results suggest that there is good agreement between the models and the CRU, in terms of their respective seasonal cycles, as shown in Taylor diagrams and bias plots. There is also good agreement between both gridded observation sets. In addition, downscaled ERA‐Interim precipitation is closer to observations than raw ERA‐Interim precipitation. Domains located in the low latitudes and those having high topography appear to have larger biases, especially precipitation.

The issue of properly ordering climate indices calculation and bias correction before identifying spatial analogs for agricultural applications - Grenier, Patrick; Firlej, Annabelle; Blondlot, Anne; Logan, Travis; Ricard, Marie-Pier (Climate Services, 2019)

Vegetation restoration stimulates soil carbon sequestration and stabilization in a subtropical area of southern China - Gu, Xiang; Fang, Xi; Xiang, Wenhua; Zeng, Yelin; Zhang, Shiji; Lei, Pifeng; Peng, Changhui; Kuzyakov, Yakov (CATENA, 2019)

Distribution margins as natural laboratories to infer species’ flowering responses to climate warming and implications for frost risk - Guo, Liang; Wang, Jinghong; Li, Mingjun; Liu, Lu; Xu, Jianchu; Cheng, Jimin; Gang, Chengcheng; Yu, Qiang; Chen, Ji; Peng, Changhui; Luedeling, Eike (Agricultural and Forest Meteorology, 2019)

Stand carbon density drivers and changes under future climate scenarios across global forests - Guo, Yanrong; Peng, Changhui; Trancoso, Ralph; Zhu, Qiuan; Zhou, Xiaolu (Forest Ecology and Management, 2019)

Modelling the impacts of climate and land use changes on soil water erosion: Model applications, limitations and future challenges - Guo, Yanrong; Peng, Changhui; Zhu, Qiuan; Wang, Meng; Wang, Han; Peng, Shushi; He, Honglin (Journal of Environmental Management, 2019)

Comparison of methane emissions among invasive and native mangrove species in Dongzhaigang, Hainan Island - He, Yixin; Guan, Wei; Xue, Dan; Liu, Liangfeng; Peng, Changhui; Liao, Baowen; Hu, Ji; Zhu, Qiu'an; Yang, Yanzhen; Wang, Xu; Zhou, Guanyi; Wu, Zhongming; et al. (Science of The Total Environment, 2019)

Land use/cover change in the Three Gorges Reservoir area, China: Reconciling the land use conflicts between development and protection - Huang, Chunbo; Huang, Xin; Peng, Changhui; Zhou, Zhixiang; Teng, Mingjun; Wang, Pengcheng (CATENA, 2019)

How is biodiversity changing in response to ecological restoration in terrestrial ecosystems? A meta-analysis in China - Huang, Chunbo; Zhou, Zhixiang; Peng, Changhui; Teng, Mingjun; Wang, Pengcheng (Science of The Total Environment, 2019)

Postglacial paleoceanography and paleoenvironments in the northwestern Barents Sea - Ivanova, Elena; Murdmaa, Ivar; De Vernal, Anne; Risebrobakken, Bjørg; Peyve, Alexander; Brice, Camille; Seitkalieva, Elvira; Pisarev, Sergey (Quaternary Research, 2019)
Abstract The Barents Sea offers a suitable location for documenting advection of warm and saline Atlantic Water (AW) into the Arctic and its impact on deglaciation and postglacial conditions. We investigate the timing, succession, and mechanisms of the transition from proximal glaciomarine to marine environment in the northwestern Barents Sea. Two studied sediment cores demonstrate diachronous retreat of the grounded ice sheet from the Kvitøya Trough (core S2528) to Erik Eriksen Trough (core S2519). Oxygen isotope records from core S2528 depict a two-step pattern, with lower δ 18 O values prior to the Younger Dryas (YD), and higher values afterward because of advection of the more saline, 18 O-enriched AW. At this location, subsurface AW penetration increased during the Allerød and YD/Preboreal transition. In the study area, foraminiferal and dinocyst data from the YD interval suggest cold conditions, extensive sea-ice cover, and brine formation, along with the flow of chilled AW at subsurface and the development of a high-productivity polynya in the Erik Eriksen Trough. Dense winter sea-ice cover with seasonal productivity persisted in the Kvitøya Trough area during the early Holocene, whereas surface warming seems to have occurred during the middle Holocene interval.

Projected change in characteristics of near surface temperature inversions for southeast Australia - Ji, Fei; Evans, Jason Peter; Di Luca, Alejandro; Jiang, Ningbo; Olson, Roman; Fita, Lluis; Argüeso, Daniel; Chang, Lisa T.-C.; Scorgie, Yvonne; Riley, Matt (Climate Dynamics, 2019)

Assessment of frozen ground organic carbon pool on the Qinghai-Tibet Plateau - Jiang, Lin; Chen, Huai; Zhu, Qiuan; Yang, Yanzheng; Li, Mingxu; Peng, Changhui; Zhu, Dan; He, Yixin (Journal of Soils and Sediments, 2019)

Does direct-seeded rice decrease ecosystem-scale methane emissions?—A case study from a rice paddy in southeast China - Li, Hong; Guo, Hai-Qiang; Helbig, Manuel; Dai, Sheng-Qi; Zhang, Meng-Shan; Zhao, Min; Peng, Chang-Hui; Xiao, Xiang-Ming; Zhao, Bin (Agricultural and Forest Meteorology, 2019)

Modeling Global Riverine DOC Flux Dynamics From 1951 to 2015 - Li, Mingxu; Peng, Changhui; Zhou, Xiaolu; Yang, Yanzheng; Guo, Yanrong; Shi, Guohua; Zhu, Qiuan (Journal of Advances in Modeling Earth Systems, 2019)
Abstract Climate change has a profound impact on the global carbon cycle, including effects on riverine carbon pools, which connect terrestrial, oceanic, and atmospheric carbon pools. Until now, terrestrial ecosystem models have rarely incorporated riverine carbon components into global carbon budgets. Here we developed a new process‐based model, TRIPLEX‐HYDRA (TRIPLEX‐hydrological routing algorithm), that considers the production, consumption, and transport processes of nonanthropogenic dissolved organic carbon (DOC) from soil to river ecosystems. After the parameter calibration, model results explained more than 50% of temporal variations in all but three rivers. Validation results suggested that DOC yield simulated by TRIPLEX‐HYDRA has a good fit ( R 2 = 0.61, n = 71, p < 0.001) with global river observations. And then, we applied this model for global rivers. We found that mean DOC yield of global river approximately 1.08 g C/m 2 year, where most high DOC yield appeared in the rivers from high northern or tropic regions. Furthermore, our results suggested that global riverine DOC flux appeared a significant decrease trend (average rate: 0.38 Pg C/year) from 1951 to 2015, although the variation patterns of DOC fluxes in global rivers are diverse. A decreasing trend in riverine DOC flux appeared in the middle and high northern latitude regions (30–90°N), which could be attributable to an increased flow path and DOC degradation during the transport process. Furthermore, increasing trend of DOC fluxes is found in rivers from tropical regions (30°S–30°N), which might be related to an increase in terrestrial organic carbon input. Many other rivers (e.g., Mississippi, Yangtze, and Lena rivers) experienced no significant changes under a changing environment. , Key Points Terrestrial ecosystem models rarely incorporate riverine DOC components into the global carbon cycle The TRIPLEX‐HYDRA model simulates the spatiotemporal variation in the DOC fluxes in global rivers The global riverine DOC flux simulated by the TRIPLEX‐HYDRA model has significantly decreased from 1951 to 2015

Nitrogen depositions increase soil respiration and decrease temperature sensitivity in a Moso bamboo forest - Li, Quan; Song, Xinzhang; Chang, Scott X.; Peng, Changhui; Xiao, Wenfa; Zhang, Junbo; Xiang, Wenhua; Li, Yan; Wang, Weifeng (Agricultural and Forest Meteorology, 2019)

Weakening of the ‘enzymatic latch’ mechanism following long-term fertilization in a minerotrophic peatland - Li, Tong; Bu, Zhaojun; Liu, Wenyan; Zhang, Mingying; Peng, Changhui; Zhu, Qiuan; Shi, Shengwei; Wang, Meng (Soil Biology and Biochemistry, 2019)

Variation in the functional traits of fine roots is linked to phylogenetics in the common tree species of Chinese subtropical forests - Liu, Cong; Xiang, Wenhua; Zou, Limei; Lei, Pifeng; Zeng, Yelin; Ouyang, Shuai; Deng, Xiangwen; Fang, Xi; Liu, Zelin; Peng, Changhui (Plant and Soil, 2019)

Comparative analyses of different biogenic CO2 emission accounting systems in life cycle assessment - Liu, Weiguo; Zhu, Qiuan; Zhou, Xiaolu; Peng, Changhui (Science of The Total Environment, 2019)

Field-experiment constraints on the enhancement of the terrestrial carbon sink by CO2 fertilization - Liu, Yongwen; Piao, Shilong; Gasser, Thomas; Ciais, Philippe; Yang, Hui; Wang, Han; Keenan, Trevor F.; Huang, Mengtian; Wan, Shiqiang; Song, Jian; Wang, Kai; Janssens, Ivan A.; et al. (Nature Geoscience, 2019)

Simulation and Analysis of the Effect of a Spruce Budworm Outbreak on Carbon Dynamics in Boreal Forests of Quebec - Liu, Zelin; Peng, Changhui; De Grandpré, Louis; Candau, Jean-Noël; Work, Timothy; Huang, Chunbo; Kneeshaw, Daniel (Ecosystems, 2019)

Mixed precipitation occurrences over southern Québec, Canada, under warmer climate conditions using a regional climate model - Matte, Dominic; Thériault, Julie M.; Laprise, René (Climate Dynamics, 2019)

On the low-frequency variability of wintertime Euro-Atlantic planetary wave-breaking - Messori, Gabriele; Davini, Paolo; Alvarez-Castro, M. Carmen; Pausata, Francesco S. R.; Yiou, Pascal; Caballero, Rodrigo (Climate Dynamics, 2019)

Effects of stand age, richness and density on productivity in subtropical forests in China - Ouyang, Shuai; Xiang, Wenhua; Wang, Xiangping; Xiao, Wenfa; Chen, Liang; Li, Shenggong; Sun, Han; Deng, Xiangwen; Forrester, David I.; Zeng, Lixiong; Lei, Pifeng; Lei, Xiangdong; et al. (Journal of Ecology, 2019)
Abstract Forest productivity may be determined not only by biodiversity but also by environmental factors and stand structure attributes. However, the relative importance of these factors in determining productivity is still controversial for subtropical forests. Based on a large dataset from 600 permanent forest inventory plots across subtropical China, we examined the relationship between biodiversity and forest productivity and tested whether stand structural attributes (stand density in terms of trees per ha, age and tree size) and environmental factors (climate and site conditions) had larger effects on productivity. Furthermore, we quantified the relative importance of environmental factors, stand structure and diversity in determining forest productivity. Diversity, together with stand structure and site conditions, regulated the variability in forest productivity. The relationship between diversity and forest productivity did not vary along environmental gradients. Stand density and age were more important modulators of forest productivity than diversity. Synthesis . Diversity had significant and positive effects on productivity in species‐rich subtropical forests, but the effects of stand density and age were also important. Our work highlights that while biodiversity conservation is often important, the regulation of stand structure can be even more important to maintain high productivity in subtropical forests.

Nitrous oxide emissions from soils under traditional cropland and apple orchard in the semi-arid Loess Plateau of China - Pang, Junzhu; Wang, Xiaoke; Peng, Changhui; Mu, Yujing; Ouyang, Zhiyun; Lu, Fei; Zhang, Hongxing; Zhang, Shuoxin; Liu, Wenzhao (Agriculture, Ecosystems & Environment, 2019)

Predicted Northward Expansion of the Geographic Range of the Tick Vector Amblyomma americanum in North America under Future Climate Conditions - Sagurova, Irina; Ludwig, Antoinette; Ogden, Nicholas H.; Pelcat, Yann; Dueymes, Guillaume; Gachon, Philippe (Environmental Health Perspectives, 2019)

Simulation of dissolved organic carbon concentrations and fluxes in Chinese monsoon forest ecosystems using a modified TRIPLEX-DOC model - Shi, Shengwei; Yang, Mingxia; Hou, Yue; Peng, Changhui; Wu, Haibin; Zhu, Qiuan; Liang, Qiong; Xie, Junfei; Wang, Meng (Science of The Total Environment, 2019)

Global soil nitrous oxide emissions since the preindustrial era estimated by an ensemble of terrestrial biosphere models: Magnitude, attribution, and uncertainty - Tian, Hanqin; Yang, Jia; Xu, Rongting; Lu, Chaoqun; Canadell, Josep G.; Davidson, Eric A.; Jackson, Robert B.; Arneth, Almut; Chang, Jinfeng; Ciais, Philippe; Gerber, Stefan; Ito, Akihiko; et al. (Global Change Biology, 2019)
Abstract Our understanding and quantification of global soil nitrous oxide (N 2 O) emissions and the underlying processes remain largely uncertain. Here, we assessed the effects of multiple anthropogenic and natural factors, including nitrogen fertilizer (N) application, atmospheric N deposition, manure N application, land cover change, climate change, and rising atmospheric CO 2 concentration, on global soil N 2 O emissions for the period 1861–2016 using a standard simulation protocol with seven process‐based terrestrial biosphere models. Results suggest global soil N 2 O emissions have increased from 6.3 ± 1.1 Tg N 2 O‐N/year in the preindustrial period (the 1860s) to 10.0 ± 2.0 Tg N 2 O‐N/year in the recent decade (2007–2016). Cropland soil emissions increased from 0.3 Tg N 2 O‐N/year to 3.3 Tg N 2 O‐N/year over the same period, accounting for 82% of the total increase. Regionally, China, South Asia, and Southeast Asia underwent rapid increases in cropland N 2 O emissions since the 1970s. However, US cropland N 2 O emissions had been relatively flat in magnitude since the 1980s, and EU cropland N 2 O emissions appear to have decreased by 14%. Soil N 2 O emissions from predominantly natural ecosystems accounted for 67% of the global soil emissions in the recent decade but showed only a relatively small increase of 0.7 ± 0.5 Tg N 2 O‐N/year (11%) since the 1860s. In the recent decade, N fertilizer application, N deposition, manure N application, and climate change contributed 54%, 26%, 15%, and 24%, respectively, to the total increase. Rising atmospheric CO 2 concentration reduced soil N 2 O emissions by 10% through the enhanced plant N uptake, while land cover change played a minor role. Our estimation here does not account for indirect emissions from soils and the directed emissions from excreta of grazing livestock. To address uncertainties in estimating regional and global soil N 2 O emissions, this study recommends several critical strategies for improving the process‐based simulations.

Changes in soil organic carbon and microbial carbon storage projected during the 21st century using TRIPLEX-MICROBE - Wang, Kefeng; Peng, Changhui; Zhu, Qiuan; Wang, Meng; Wang, Gangsheng; Zhou, Xiaolu; Yang, Yanzheng; Ding, Juhua; Wei, Hua (Ecological Indicators, 2019)

Structural and functional differentiation of the microbial community in the surface and subsurface peat of two minerotrophic fens in China - Wang, Meng; Tian, Jianqing; Bu, Zhaojun; Lamit, Louis J.; Chen, Huai; Zhu, Qiuan; Peng, Changhui (Plant and Soil, 2019)

Enhanced Himalayan Glacial Melting During YD and H1 Recorded in the Northern Bay of Bengal - Weldeab, Syee; Rühlemann, Carsten; Bookhagen, Bodo; Pausata, Francesco S. R.; Perez‐Lua, Fabiola M. (Geochemistry, Geophysics, Geosystems, 2019)
Abstract Ocean‐land thermal feedback mechanisms in the Indian Summer Monsoon (ISM) domain are an important but not well understood component of regional climate dynamics. Here we present a δ 18 O record analyzed in the mixed‐layer dwelling planktonic foraminifer Globigerinoides ruber ( sensu stricto ) from the northernmost Bay of Bengal (BoB). The δ 18 O time series provides a spatially integrated measure of monsoonal precipitation and Himalayan meltwater runoff into the northern BoB and reveals two brief episodes of anomalously low δ 18 O values between 16.3±0.4 and 16±0.5 and 12.6±0.4 and 12.3±0.4 thousand years before present. The timing of these events is centered at Heinrich event 1 and the Younger Dryas, well‐known phases of weak northern hemisphere monsoon systems. Numerical climate model experiments, simulating Heinrich event‐like conditions, suggest a surface warming over the monsoon‐dominated Himalaya and foreland in response to ISM weakening. Corroborating the simulation results, our analysis of published moraine exposure ages in the monsoon‐dominated Himalaya indicates enhanced glacier retreats that, considering age model uncertainties, coincide and overlap with the episodes of anomalously low δ 18 O values in the northernmost BoB. Our climate proxy and simulation results provide insights into past regional climate dynamics, suggesting reduced cloud cover, increased solar radiation, and air warming of the Himalaya and foreland areas and, as a result, glacier mass losses in response to weakened ISM. , Plain Language Summary Indian Summer Monsoon rainfall and Himalayan glacier/snow melts constitute the main water source for the densely populated Indian subcontinent. Better understanding of how future climate changes will affect the monsoon rainfall and Himalayan glaciers requires a long climate record. In this study, we create a 13,000‐year‐long climate record that allows us to better understand the response of Indian Summer Monsoon rainfall and Himalayan glaciers to past climate changes. The focus of our study is the time window between 9,000 and 22,000 years ago, an episode where the global climate experienced large and rapid changes. Our sediment record from the northern Bay of Bengal and climate change simulation indicate that during episodes of weak monsoon, the melting of the Himalayan glaciers increases substantially significantly. This is because the weakening of the monsoon results in less cloud cover and, as a result, the surface receives more sunlight and causes glacier melting. , Key Points Core sediments from the northern Bay of Bengal are a viable archive to reconstruct past changes in monsoonal and Himalayan meltwater runoff Weak monsoon reduces cloud cover and leads to increased radiative flux over the Himalaya and foreland areas and causes glacier mass loss A spatially integrated record of monsoon and Himalayan climate provides insights into regional climate dynamics

Modeling and estimating aboveground biomass of Dacrydium pierrei in China using machine learning with climate change - Wu, Chunyan; Chen, Yongfu; Peng, Changhui; Li, Zhaochen; Hong, Xiaojiang (Journal of Environmental Management, 2019)

Linkage between tree species richness and soil microbial diversity improves phosphorus bioavailability - Wu, Huili; Xiang, Wenhua; Ouyang, Shuai; Forrester, David I.; Zhou, Bo; Chen, Lingxiu; Ge, Tida; Lei, Pifeng; Chen, Liang; Zeng, Yelin; Song, Xinzhang; Peñuelas, Josep; et al. (Functional Ecology, 2019)
Abstract Increased availability of soil phosphorus (P) has recently been recognised as an underlying driving factor for the positive relationship between plant diversity and ecosystem function. The effects of plant diversity on the bioavailable forms of P involved in biologically mediated rhizospheric processes and how the link between plant and soil microbial diversity facilitates soil P bioavailability, however, remain poorly understood. This study quantified four forms of bioavailable P (CaCl 2 ‐P, citric‐P, enzyme‐P and HCl‐P) in mature subtropical forests using a novel biologically based approach, which emulates how rhizospheric processes influence the release and supply of available P. Soil microbial diversity was measured by Illumina high‐throughput sequencing. Our results suggest that tree species richness significantly affects soil microbial diversity ( p < 0.05), increases litter decomposition, fine‐root biomass and length and soil organic carbon and thus increases the four forms of bioavailable P. A structural equation model that links plants, soil microbes and P forms indicated that soil bacterial and fungal diversity play dominant roles in mediating the effects of tree species richness on soil P bioavailability. An increase in the biodiversity of plants, soil bacteria and fungi could maintain soil P bioavailability and alleviate soil P limitations. Our results imply that biodiversity strengthens plant and soil feedback and increases P recycling. A plain language summary is available for this article.

The effects of persistent drought and waterlogging on the dynamics of nonstructural carbohydrates of Robinia pseudoacacia L. seedlings in Northwest China - Yang, Bin; Peng, Changhui; Zhu, Qiuan; Zhou, Xiaolu; Liu, Weiguo; Duan, Min; Wang, Hui; Liu, Zhihao; Guo, Xinyi; Wang, Meng (Forest Ecosystems, 2019)

Peatland degradation reduces methanogens and methane emissions from surface to deep soils - Yang, Gang; Tian, Jianqing; Chen, Huai; Jiang, Lin; Zhan, Wei; Hu, Ji; Zhu, Erxiong; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; He, Yixin; Li, Mingxu; et al. (Ecological Indicators, 2019)

Immediate and carry-over effects of increased soil frost on soil respiration and microbial activity in a spruce forest - Yang, Kaijun; Peng, Changhui; Peñuelas, Josep; Kardol, Paul; Li, Zhijie; Zhang, Li; Ni, Xiangyin; Yue, Kai; Tan, Bo; Yin, Rui; Xu, Zhenfeng (Soil Biology and Biochemistry, 2019)

Quantifying leaf‐trait covariation and its controls across climates and biomes - Yang, Yanzheng; Wang, Han; Harrison, Sandy P.; Prentice, I. Colin; Wright, Ian J.; Peng, Changhui; Lin, Guanghui (New Phytologist, 2019)
Summary Plant functional ecology requires the quantification of trait variation and its controls. Field measurements on 483 species at 48 sites across China were used to analyse variation in leaf traits, and assess their predictability. Principal components analysis ( PCA ) was used to characterize trait variation, redundancy analysis ( RDA ) to reveal climate effects, and RDA with variance partitioning to estimate separate and overlapping effects of site, climate, life‐form and family membership. Four orthogonal dimensions of total trait variation were identified: leaf area ( LA ), internal‐to‐ambient CO 2 ratio (χ), leaf economics spectrum traits (specific leaf area ( SLA ) versus leaf dry matter content ( LDMC ) and nitrogen per area ( N area )), and photosynthetic capacities ( V cmax , J max at 25°C). LA and χ covaried with moisture index. Site, climate, life form and family together explained 70% of trait variance. Families accounted for 17%, and climate and families together 29%. LDMC and SLA showed the largest family effects. Independent life‐form effects were small. Climate influences trait variation in part by selection for different life forms and families. Trait values derived from climate data via RDA showed substantial predictive power for trait values in the available global data sets. Systematic trait data collection across all climates and biomes is still necessary.

Responses of nitrogen concentrations and pools to multiple environmental change drivers: A meta‐analysis across terrestrial ecosystems - Yue, Kai; Peng, Yan; Fornara, Dario A.; Van Meerbeek, Koenraad; Vesterdal, Lars; Yang, Wanqin; Peng, Changhui; Tan, Bo; Zhou, Wei; Xu, Zhenfeng; Ni, Xiangyin; Zhang, Li; et al. (Global Ecology and Biogeography, 2019)
Abstract Aim We sought to understand how the individual and combined effects of multiple environmental change drivers differentially influence terrestrial nitrogen (N) concentrations and N pools and whether the interactive effects of these drivers are mainly antagonistic, synergistic or additive. Location Worldwide. Time period Contemporary. Major taxa studied Plants, soil, and soil microbes in terrestrial ecosystems. Methods We synthesized data from manipulative field studies from 758 published articles to estimate the individual, combined and interactive effects of key environmental change drivers (elevated CO 2 , warming, N addition, phosphorus addition, increased rainfall and drought) on plant, soil, and soil microbe N concentrations and pools using meta‐analyses. We assessed the influences of moderator variables on these effects through structural equation modelling. Results We found that (a) N concentrations and N pools were significantly affected by the individual and combined effects of multiple drivers, with N addition (either alone or in combination with another driver) showing the strongest positive effects; (b) the individual and combined effects of these drivers differed significantly between N concentrations and N pools in plants, but seldom in soils and microbes; (c) additive effects of driver pairs on N concentrations and pools were much more common than synergistic or antagonistic effects across plants, soils and microbes; and (d) environmental and experimental factors were important moderators of the individual, combined and interactive effects of these drivers on terrestrial N. Main conclusions Our results indicate that terrestrial N concentrations and N pools, especially those of plants, can be significantly affected by the individual and combined effects of environmental change drivers, with the interactive effects of these drivers being mostly additive. Our findings are important because they contribute to the development of models to better predict how altered N availability affects ecosystem carbon cycling under future environmental changes.

The impact of secondary forest restoration on multiple ecosystem services and their trade-offs - Zeng, Yelin; Gou, Mengmeng; Ouyang, Shuai; Chen, Liang; Fang, Xi; Zhao, Lijuan; Li, Jiaxiang; Peng, Changhui; Xiang, Wenhua (Ecological Indicators, 2019)

Spatial and temporal variations of N2O emissions from global forest and grassland ecosystems - Zhang, Kerou; Zhu, Qiuan; Liu, Jinxun; Wang, Meng; Zhou, Xiaolu; Li, Mingxu; Wang, Kefeng; Ding, Juhua; Peng, Changhui (Agricultural and Forest Meteorology, 2019)

Re-estimating the changes and ranges of forest biomass carbon in China during the past 40 years - Zhou, Xiaolu; Lei, Xiangdong; Liu, Caixia; Huang, Huabing; Zhou, Carl; Peng, Changhui (Forest Ecosystems, 2019)
Abstract Background In recent decades the future of global forests has been a matter of increasing concern, particularly in relation to the threat of forest ecosystem responses under potential climate change. To the future predictions of these responses, the current forest biomass carbon storage (FCS) should first be clarified as much as possible, especially at national scales. However, few studies have introduced how to verify an FCS estimate by delimiting the reasonable ranges. This paper addresses an estimation of national FCS and its verification using two-step process to narrow the uncertainty. Our study focuses on a methodology for reducing the uncertainty resulted by converting from growing stock volume to above- and below-ground biomass (AB biomass), so as to eliminate the significant bias in national scale estimations. Methods We recommend splitting the estimation into two parts, one part for stem and the other part for AB biomass to preclude possible significant bias. Our method estimates the stem biomass from volume and wood density (WD), and converts the AB biomass from stem biomass by using allometric relationships. Results Based on the presented two-step process, the estimation of China’s FCS is performed as an example to explicate how to infer the ranges of national FCS. The experimental results demonstrate a national FCS estimation within the reasonable ranges (relative errors: + 4.46% and − 4.44%), e.g., 5.6–6.1 PgC for China’s forest ecosystem at the beginning of the 2010s. These ranges are less than 0.52 PgC for confirming each FCS estimate of different periods during the last 40 years. In addition, our results suggest the upper-limits by specifying a highly impractical value of WD (0.7 t∙m − 3 ) on the national scale. As a control reference, this value decides what estimate is impossible to achieve for the FCS estimates. Conclusions Presented methodological analysis highlights the possibility to determine a range that the true value could be located in. The two-step process will help to verify national FCS and also to reduce uncertainty in related studies. While the true value of national FCS is immeasurable, our work should motivate future studies that explore new estimations to approach the true value by narrowing the uncertainty in FCS estimations on national and global scales.

Factors Affecting the Spatial and Temporal Variations in Soil Erodibility of China - Zhu, Guangyu; Tang, Zhuangsheng; Shangguan, Zhouping; Peng, Changhui; Deng, Lei (Journal of Geophysical Research: Earth Surface, 2019)
Abstract Soil erosion occurs extensively across China, leading to severe degradation of the land and ecosystem services. However, the spatial and temporal variations in soil erodibility ( k ) and the distribution of soil erosion across land use types and slopes remain unclear. We synthesized the results from 325 sites published in 152 literatures to analyze the factors affecting the k , such as land use type, climate, topography, soil, and vegetation restoration age. The results showed that areas with slopes >25° had a larger k factor ( k = 0.1047) than did those with slope <6° ( k = 0.0637) or 6–25° ( k = 0.0832). The k from 2006 to 2011 ( k = 0.0725) was higher than that from 1999 to 2005 ( k = 0.058) and that from 2012 to 2016 ( k = 0.0631). The k value initially increased with vegetation restoration age and then gradually decreased. Land use also had an impact on the k factor, with the k factor of cropland ( k = 0.0697) being higher than that of grassland ( k = 0.0663) but lower than that of forest ( k = 0.0967). Across China, North Shaanxi, Heilongjiang, and South Guizhou, which are located in the Loess Plateau in Northwest China, the Black Soil region of Northeast China, and the Karst areas in Southwest China, respectively, were the three most severely eroded regions due to hydraulic erosion, frost‐thaw erosion, and high‐intensity erosion, respectively. Overall, the most important factors affecting the k were soil characteristics, followed by topography and climate. Among them, soil nitrogen and precipitation were the two most critical factors influencing the k . , Key Points Grassland had lower soil erodibility than had cropland and forestland North Shaanxi, Heilongjiang, and South Guizhou were the three most severely eroded regions Precipitation and soil N play critical roles in controlling soil erosion

Impagidinium detroitense and I.? diaphanum: Two new dinoflagellate cyst species from the Pliocene of the North Pacific Ocean, and their biostratigraphic significance - Zorzi, Coralie; Head, Martin J.; Matthiessen, Jens; De Vernal, Anne (Review of Palaeobotany and Palynology, 2019)